Smart Grid Solutions for Loss Minimization and Voltage Profile Enhancement using Genetic Algorithm-Optimized Capacitor and Solar PV Integration in Radial Feeder - Poudel, Yam Krishna (Journal of Engineering Issues and Solutions, 2025)
This research addresses the critical issue of power losses in electrical distribution systems, a challenge that has intensified with the rising electricity demand. The study focuses on minimizing these losses and improving voltage profiles within a radial distribution network through the optimal placement of capacitors and solar photovoltaic (PV) systems. A comprehensive methodological framework is employed, integrating load flow analysis via the forward and backward sweep algorithms and optimization using the Genetic Algorithm (GA) implemented in MATLAB.Key performance indicators such as active and reactive power losses, along with voltage profile characteristics, are used to assess the effectiveness of various configurations. Simulation studies conducted on the standard IEEE 33-bus radial distribution network demonstrate significant improvements across multiple scenarios—namely, the base case, capacitor-only case, distributed generation (DG)-only case, and a combined DG-capacitor case. In each configuration, notable reductions in power losses and enhancements in voltage stability are observed.The findings are further substantiated through validation in ETAP software, reinforcing the accuracy and reliability of the results. Moreover, the practical feasibility of the proposed approach is demonstrated through a case analysis of the Thimi-Sallaghari 11 kV feeder, revealing promising implications for real-world implementation. The study also explores various deployment scenarios involving up to three units of capacitors and DGs, offering valuable insights into the optimal integration strategy for enhanced distribution system performance